Perspectives on the mechanism of pyroptosis after intracerebral hemorrhage - Song, Dengpan; Yeh, Chi-Tai; Wang, Jian; Guo, Fuyou (Frontiers in Immunology, 2022)
Intracerebral hemorrhage (ICH) is a highly harmful neurological disorder with high rates of mortality, disability, and recurrence. However, effective therapies are not currently available. Secondary immune injury and cell death are the leading causes of brain injury and a poor prognosis. Pyroptosis is a recently discovered form of programmed cell death that differs from apoptosis and necrosis and is mediated by gasdermin proteins. Pyroptosis is caused by multiple pathways that eventually form pores in the cell membrane, facilitating the release of inflammatory substances and causing the cell to rupture and die. Pyroptosis occurs in neurons, glial cells, and endothelial cells after ICH. Furthermore, pyroptosis causes cell death and releases inflammatory factors such as interleukin (IL)-1β and IL-18, leading to a secondary immune-inflammatory response and further brain damage. The NOD-like receptor protein 3 (NLRP3)/caspase-1/gasdermin D (GSDMD) pathway plays the most critical role in pyroptosis after ICH. Pyroptosis can be inhibited by directly targeting NLRP3 or its upstream molecules, or directly interfering with caspase-1 expression and GSDMD formation, thus significantly improving the prognosis of ICH. The present review discusses key pathological pathways and regulatory mechanisms of pyroptosis after ICH and suggests possible intervention strategies to mitigate pyroptosis and brain dysfunction after ICH.